Andrographolide engineered gold nanoparticle to overcome drug resistant visceral leishmaniasis. (31st October 2018) - Das, Suvadra; Halder, Asim; Mandal, Saptarshi; Mazumder, Mohammad Abu Jafar; Bera, Tanmoy; Mukherjee, Arup; Roy, Partha
Abstract: Visceral leishmaniasis (VL) is World Health Organization designated most serious leishmaniasis with an annual mortality rate of 50, 000. Even after country specific eradication programs, the disease continues to multiply with added complexities like resistance development, drug hypersensitivity and associated infections. Newer therapeutic interventions are urgently warranted to control the spread. Present study aims to arrive at terpenoid andrographolide engineered gold nanoparticle (AGAunps) facile synthesis and its efficacy evaluations against wild and drug resistant VL strains for the first time. Molecular bio-organic conjugation of AGAunp was confirmed in FT-IR and EDAX studies. Nano-gold plasmon response was recorded at 543 nm and the average size in TEM was 14 nm. SAED pattern and XRD observations proved fcc crystalline structure of nano-gold. AGAunp recorded spherical geometry in AFM and TEM. PDI value of 0.137 revealed the monodisperse nature of the nano-scale population. AGAunp exhibited strong antileishmanicidal effect both against wild type (IC50 19 ± 1.7 µM) and sodium stibogluconate (IC50 55 ± 7.3 µM)/paromomycin (IC50 41 ± 6 µM) resistant strains. Complete macrophage uptake AGAunp's occured within two hours exposure. AGAunp macrophage cytotoxicity was significantly lower as compared to Amphotericin-B. Low toxic Andrographolide engineered gold nanoparticle emerged as promising alternatives in the control of wild and drug resistant VL. Graphical Abstract: UF0001